Notes on taxonomy, distribution and conservation of Dichaea species (Orchidaceae: Zygopetalinae) in Brazilian Amazon - Krahl, Dayse R. P.; Chiron, Guy; Krahl, Amauri H.; Da Silva, João Batista F.; Cantuária, Patrick De C. (Phytotaxa, 2024)
In this article we first propose to treat Dichaea integrilabia and D. saraca-taquerensis as synonyms based on analysis of the types, original descriptions and other material conserved in Amazonian herbaria. We also better address the taxonomic issues relating to D. fusca and D. weigeltii which have been wrongly considered as synonymous species. Besides we document the geographical expansion of D. fusca to the state of Pará (Brazil) whereas it was hitherto thought to be restricted to the state of Amazonas (Brazil). For both taxa (D. saraca-taquerensis and D. fusca) we give a taxonomic description, a photograph plate, information about the geographical distribution (with a map) as well as a preliminary conservation status according to IUCN criteria.